Cybersecurity In The Digital Age: Developing Robust Strategies To Protect Against Evolving Global Digital Threats And Cyber Attacks - Sendjaja, Theodorus; Irwandi; Prastiawan, Erwan; Suryani, Yunita; Fatmawati, Endang (GoAcademica Research & Publishing, 2024)
In today's digital era, cyber security is a growing challenge, considering increasingly sophisticated cyber attacks and increasing global digital threats. These threats not only pose risks to individual privacy but also to the security of critical infrastructure and the country's economic interests. The need to develop a robust and adaptive cybersecurity strategy is critical to protecting digital assets and maintaining information security. This research aims to analyze the global cyber threat landscape and develop effective cyber security strategies to counter evolving digital threats. The method used is a descriptive qualitative approach by collecting and analyzing data from relevant previous studies. The results of the research show that an effective cybersecurity strategy requires an adaptive and innovative approach, utilizing the latest technology and cross-sector collaboration. The importance of international collaboration and human resource development in the field of cyber security was emphasized as a key factor in building stronger defenses against cyber attacks. Analysis of global cyber threats and their threat actors provides insight into the importance of cybersecurity education and awareness at all levels of organizations and society. The security strategy developed must be able to adapt to changes in technology and attack tactics to ensure effective protection. Cross-sector collaboration and the development of a strong cybersecurity ecosystem are the foundations for facing future cybersecurity challenges.